1983
DOI: 10.1002/cjce.5450610121
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of temperature peak attenuation by catalyst dilution in a tubular packed‐bed reactor

Abstract: Temperature peak attenuation is an important problem for safe process control. Simulations of the axial temperature and product progression in stationary ammonia synthesis with different axial catalyst dilutions have been carried out. It is demonstrated that the requirement of temperature peak attenuation together with a maximum product yield can be met by an optimal catalyst dilution profile at the entrance of the bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…With only catalyst pellets inside a reactor and no inert pellets, if the jacket temperature is increased in order to achieve a high yield, it can lead to an excessive peak temperature, lowering the overall yield. However, if inert pellets are mixed with catalyst pellets where hot spots occur, it is possible to produce a higher yield without increasing the peak temperature in a reactor (Danziger et al, 1983;Ferreira, 1999a, 2000). Beyond this application to heterogeneous catalytic reactors, catalyst dilution can also be applied to trickle-flow reactors but with different objectives.…”
Section: Catalyst Dilutionmentioning
confidence: 98%
See 2 more Smart Citations
“…With only catalyst pellets inside a reactor and no inert pellets, if the jacket temperature is increased in order to achieve a high yield, it can lead to an excessive peak temperature, lowering the overall yield. However, if inert pellets are mixed with catalyst pellets where hot spots occur, it is possible to produce a higher yield without increasing the peak temperature in a reactor (Danziger et al, 1983;Ferreira, 1999a, 2000). Beyond this application to heterogeneous catalytic reactors, catalyst dilution can also be applied to trickle-flow reactors but with different objectives.…”
Section: Catalyst Dilutionmentioning
confidence: 98%
“…In this work, the catalyst is assumed to be well mixed enough to prevent bypass in a reactor zone. Also, it should be noted that the use of inert pellets affects the heat Table 1 Researches on various reactions using catalyst dilution Authors Reaction Ferreira (2000, 1999a,b) Partial oxidation of methanol to formaldehyde over iron/molybdenum-oxides catalyst Choudhary and Mamman (1999) Oxidative conversion of methane to syngas over NiO/MgO supported on Silica-alumina pellet Danziger et al (1983) Ammonia synthesis Sadhukhan and Petersen (1976) Oxidation of naphthalene Caldwell and Calderbank (1969) Oxidation of O-xylene and mass transfer characteristics in a reactor according to the pellet size and geometry. However, these effects require very detailed investigation and should be considered at the final stage of reactor design.…”
Section: Catalyst Dilutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, these processes have been carried out in fixed bed reactors packed with catalysts where both exothermic and endothermic reactions occur together. Controlling the reactor temperature is very crucial for optimum reactor performance, and a number of methods have been studied for this aim. For an exothermic reversible reaction, the temperature may be controlled directly by bypassing cold feed around main feed preheater and distributing it along the length of the reactor. , Another method is cold stream injection that cools the bulk reacting fluid . The above operations require an optimal policy in rate of addition of cold feed such that the reaction rate is maximized with respect to variation of the mass flow rate at each point of the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…It establishes specific temperature profiles (both in the radial and axial directions) in the packed-bed reactor and thereby improves the isothermicity while simultaneously suppressing other effects that adversely affect performance (e.g., nature of axial dispersion, channeling loss). The strategy of dilution by solids has been studied to improve packed-bed reactor performance and is now being increasingly applied. , The cost of catalyst forms a major component in reactor operation, and dilution can help in this aspect. In addition to packed-bed catalytic reactors, catalyst dilution by solids has been applied to fluidized-bed reactors , and trickle-bed reactors. , Care should be taken, however, to prevent bypass of flow inside a reactor while employing the dilution strategy. Catalyst dilution studies reported in the literature use inert solid−catalyst mixtures.…”
Section: Introductionmentioning
confidence: 99%